Climatic and geographic barriers drive distributional patterns of bird phenotypes within peninsular India. (18th January 2017) - Ramachandran, Vivek; Robin, V. V.; Tamma, Krishnapriya; Ramakrishnan, Uma
Abstract : Modern phylogenetic data provide unparalleled ability to test biogeographic paradigms, often suggested by differences in species distribution patterns. However, such approaches have been applied less at regional scales, particularly in Asia. In the absence of such data, we examine if concordance of distributional patterns for phenotypes (subspecies) suggest potential biogeographic barriers for birds in peninsular India. Specifically, we examine climatic and physical factors that might limit phenotype distributions in this region. Various physical, vegetation and climatic barriers were demarcated to identify potential biogeographic units within peninsular India. We then collated occurrence of endemic or disjunctly distributed species and subspecies within these units using published range maps. We also quantified turnover between potential units, allowing us to identify significant biogeographic barriers. Three time‐step climate data (Last Glacial Maxima, mid‐Holocene and present) enabled us to examine differences between these potential biogeographic regions through time. The Palk Straits, followed by the Goa Gap (∼ 16°N) and the Godavari River emerged as the major barriers in this region. The Palk Straits and Godavari are physical barriers while Goa Gap appears to be a climate‐mediated ecological divide. Mountain barriers like the Palghat Gap are not the most significant barriers as previously thought. Climatically intermediate regions appeared unstable in the past and showed inconsistent affinities to different geographic units across families. We suggest that relative climatic stability of the wet regions of the southern western Ghats could be responsible for high subspecies endemism here. Our approach provides hypotheses that can be tested with comparative multi‐species phylogeographic data in the future.